(untitled) (Brazilian Geographical Journal, 2019)
Sunshine is another climatic parameter that may improve our knowledge of the changing climate. Sunshine intensity has theoretically been linked to changes in atmospheric circulation patterns. We attempt empirical linkage of diurnal changes in sunshine intensity to the energy-water budget indicative of environmental changes. Considering six stations (Abuja, Enugu, Port Harcourt, Sokoto, Ikeja and Maiduguri) each representing geopolitical zones of Nigeria, as independent homogenous units of local climate, the mean diurnal sunshine intensity for January 1, 2006 to December 31, 2014 was analysed. The effect of insolation on some atmospheric predictor variables derived from satellite data generated using the NASA Goddard Earth Observing System - Version 1 (GEOS-1) Multiyear Assimilation Timeseries Data, was examined with linear regression and Pearson’s correlation techniques. Result of the diurnal sunshine analysis of variance show significant differences for all the stations with the exception of the Maiduguri, suggesting a year-round heterogeneous sunshine intensity. However, the diurnal sunshine time series analysis indicated no significant difference for both Port Harcourt and Ikeja with Ljung Box Q values of 33.08 and 37.30 respectively. While daylight cloud amount and precipitation strongly correlated with top of atmosphere insolation in all the six stations, the partial curve fit models derived for each local climate showed that the effect of sunshine is more on the hydrometeorological components than on temperature and heat budget. These findings improve understanding of local radiation climatology, although, further studies could help to develop new methods to downscale General Circulation Models of climate change for the region.